Exploring Conversational Programming through the CHOP Paradigm and Artificial Intelligence - Alin ZAMFIROIU; Costinela-Beatrice PASTINICA; Catalin CRACIUN; Claudia CIUTACU; Theodor LUCA (Informatică economică)
Chat-Oriented Programming (CHOP) is an emerging conceptual approach to programming, focused on the interaction between programmers and conversational interfaces based on artificial intelligence (AI). Unlike the traditional paradigm, centered on writing code directly, CHOP proposes a software development model in which application components are built, modified, and analyzed through natural dialogues with AI agents. The goal of this paradigm is to reduce technical barriers and transform the programming process into a collaborative, conversational, and more accessible act. The paper explores techniques for automatic code generation assisted by artificial intelligence, highlighting a series of tools and platforms relevant to the Chat-Oriented Programming (CHOP) paradigm. It also analyzes the benefits of this approach in optimizing the software development process.